Assessing Lexical Psychological Properties in Second Language Production: A Dynamic Semantic Similarity Approach - Sun, Kun; Lu, Xiaofei (Frontiers in Psychology, 2021)
Previous studies of the lexical psycholinguistic properties (LPPs) in second language (L2) production have assessed the degree of an LPP dimension of an L2 corpus by computing the mean ratings of unique content words in the corpus for that dimension, without considering the possibility that learners at different proficiency levels may perceive the degree of that dimension of the same words differently. This study extended a dynamic semantic similarity algorithm to estimate the degree of five different LPP dimensions of several sub-corpora of the Education First - Cambridge Open Language Database (EFCAMDAT2) representing L2 English learners at different proficiency levels. Our findings provide initial evidence for the reliability of the algorithm for assessing the LPPs in L2 production and contribute useful insights into between-proficiency relationships and cross-proficiency differences in the LPPs in L2 production as well as the relationships among different LPP dimensions.